CONTRIBUTION OF ANIMAL HUSBANDRY SECTOR TO THE INCOME OF BINJAI CITY REGION AND THE FACTOR THAT EFFECTS IT - adha, apritama -; Ayu, Sri Fajar; Budi, Usman (Fakultas Peternakan, Universitas Padjadjaran, 2023)
Modern era requires economic wheels to grow each year. Every regional government must have its own source of income in order to be self-sustain to their economy and not too depended to the central goverment. Therefor the government official needs to improve their regional sector to generate more income. this thesis will mainly discuss Animal Husbandry sector. Animal Husbandry sector generate income using its own slaughter house as the main source, the method to determine how impactfull the sector to the overall income of the region are 1. Contribution Analysists: to analyse the impact of the sector to overall income. 2. Growth Analysist: to analyse the growth of the income to overall income in each year. 3. Multiple Regression Analysist: to know what factor effect the sector income. The result of the method are 1. The contribution is low due to the pandemic that cause the production number to decrease. 2. The growth of sector income also decrease because of COVID19 pandemic, the pandemic cause Indonesian government to impant PPKM, a movement restriction that make the production, distribution and marketing have a decrease. 3. The 3 factor that analyzed: Livestock number slaughtered in binjai slaughter house, meat production, and population growth are all have significant positive impact to the animal husbandry sector